(untitled) (Scientific journal of the Fergana State University, 2024)
The article discusses and summarizes the preliminary materials collected on the breeding ecology and importance of the Indian sparrow-Passer indicus in Uzbekistan. Distribution of the Indian sparrow in Uzbekistan, its meeting characteristics, specific characteristics of its reproduction and its importance in agriculture have been studied. Based on the results of studying the role of this species in nature and in agriculture, recommendations on the measures to be implemented in order to manage the behavior have been developed.